Antioxidant activity of brown algae extract (Sargassum sp): A review - Riwanti, Pramudita; Mahmiah, Mahmiah; Juniar, Kiki (Science Midwifery, 2024)
Free radicals are compounds that trigger oxidative stress and harm human health. Uncontrolled oxidative stress causes several degenerative diseases. Antioxidants are needed to prevent or reduce oxidative stress. One of the plants with a high content of antioxidant compounds is brown algae (Sargassum sp). The study aimed to examine Sargassum sp.'s antioxidant activity, which is expressed in the IC50 value using the DPPH method as measured by a UV-Vis spectrophotometer. It is a narrative review, with literature searches from the Science Direct, Pubmed, and Google Scholar databases. The results showed that the methanol extract of Sargassum sp. has strong antioxidant activity consisting of phenolic compounds, flavonoids, and carotenoids. This review concludes that Sargassum sp extract has antioxidant activity.